Managers, can you hear me now? [ hard-hitting lessons on how to get real results - Strigl, Denny F.; Swiatek, Frank (McGraw-Hill, 2011)
The man who made Verizon #1 in wireless teaches managers how to how to drive results, develop people, and build careers